The Relationship between Subnormal Peak-Stimulated Growth Hormone Levels and Auxological Characteristics in Obese Children - Barrett, Jefferson; Maranda, Louise; Nwosu, Benjamin U. (Frontiers in Endocrinology, 2014)
Context: The hypothesis that obese children are overdiagnosed with growth hormone deficiency (GHD) has not been adequately investigated in the context of adiposity-related differences in auxology. Aim: To investigate the differences in auxological parameters between short, prepubertal, obese children, and normal-weight peers who underwent growth hormone stimulation testing (GHST). Hypothesis: Over-weight/obese children with GHD [peak growth hormone (GH) < 10 μg/L] will have higher values for growth velocity (GV) standard deviation score (SDS), bone age minus chronological age (BA − CA), and child height SDS minus mid-parental height (MPTH) SDS when compared to normal-weight GHD peers. Subjects and Methods: A retrospective review of anthropometric and provocative GHST data of 67 prepubertal, GH-naïve children of age 10.21 ± 2.56 years (male n = 45, age 10.8 ± 2.60 years; female n = 22, age 8.94 ± 2.10). Inclusion criteria: GHST using arginine and clonidine. Exclusion criteria: hypopituitarism, abnormal pituitary magnetic resonance imaging scan, syndromic obesity, or syndromic short stature. Data were expressed as mean ± SD. Results: The over-weight/obese children with peak GH of <10 μg/L had significantly lower value for natural log (ln) peak GH (1.45 ± 0.09 vs. 1.83 ± 0.35, p = 0.022), but similar values for GV SDS, insulin-like growth factor-I, insulin-like growth factor binding protein-3, bone age, BA − CA, MPTH, and child height SDS minus MPTH SDS compared to normal-weight peers with GHD. After adjusting for covariates, the over-weight/obese children (BMI ≥ 85th percentile) were >7 times more likely than normal-weight subjects (BMI < 85th percentile) to have a peak GH of <10 μg/L, and 23 times more likely to have a peak GH of <7 μg/L (OR = 23.3, p = 0.021). There was a significant inverse relationships between BMI SDS and the ln of peak GH (β = −0.40, r2 = 0.26, p = 0.001), but not for BMI SDS vs. GV SDS, ln peak GH vs. BA, or ln peak GH vs. GV SDS. Conclusion: Subnormal peak GH levels in obese prepubertal children are not associated with unique pre-GHST auxological characteristics.